Florida Avocado Production and Profitability Analysis - Edward A. Evans (EDIS)
This article provides an estimate of the costs and returns associated with avocado production in Miami-Dade County and a brief analysis of the profitability of the industry. The budget is based on a 5-year average yield of 8,000 pounds per acre (assuming a pack-out rate of 94%) and on estimates of the current average F.O.B. price in South Florida of $0.85 per pound. The budget does not make any provision for establishment costs. Although the assumptions made in computing the costs reflect the practices of the avocado growers in the area, the information provided here is intended only as a guide to facilitate estimating the financial requirements of maintaining avocado groves. Data used in the analysis were obtained from interviews with growers and Extension specialists. This is EDIS document FE575, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published November 2005.